2018
DOI: 10.3399/bjgpopen18x101469
|View full text |Cite
|
Sign up to set email alerts
|

What GPs mean by 'spirituality' and how they apply this concept with patients: a qualitative study

Abstract: BackgroundLittle is known about how the concept of spirituality is understood and applied by GPs.AimTo provide a detailed description of how GPs understand the concept of spirituality and apply this with patients.Design & settingNineteen Scottish GPs were interviewed about their perceptions of the concept of spirituality and how they apply this in practice.MethodAn approach informed by grounded theory was used to identify and summarise common themes.ResultsSeven concepts concerning spirituality emerged, some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…1,3 GPs' diverse conceptions of spirituality are likely to influence their attitudes towards spiritual care and give rise to a wide range of practices. 8 Although GPs are free to apply the model of their choice, as all are satisfactory, the collaborative one offers a particularly far-reaching vision. However, its lack of application calls its relevance to the healthcare system into question.…”
Section: Collaborativementioning
confidence: 99%
“…1,3 GPs' diverse conceptions of spirituality are likely to influence their attitudes towards spiritual care and give rise to a wide range of practices. 8 Although GPs are free to apply the model of their choice, as all are satisfactory, the collaborative one offers a particularly far-reaching vision. However, its lack of application calls its relevance to the healthcare system into question.…”
Section: Collaborativementioning
confidence: 99%
“…GPs were not made aware of this survey or a detailed programme prior to attendance and it is unlikely that any attended out of a specific interest in spirituality. The structured written questionnaire was prepared using concepts and themes developed from our previous qualitative study (16) and used Likert scales of agreement and free text as per Bryman. (19) Face and construct validity were judged to be high because of the derivation of concepts from previous studies, the use of standard methodologies, triangulation of the data to other studies using different methodologies, and the fact that respondents did not offer alternative themes or categories as free text.…”
Section: Methodsmentioning
confidence: 99%
“…Progress has been made towards consensus definitions for spirituality in health care, for example that published by Puchalski: "Spirituality is the aspect of humanity that refers to the way individuals seek and express meaning and purpose and the way they experience their connectedness to the moment, to self, to others, to nature, and to the significant or sacred," (15) However, our previous qualitative work suggests that despite this there are large variations in how this concept is understood and applied clinically, including in primary care. (16,17) Little is known about GP training adequacy apart from one study which investigated and reported very low levels of training in spiritual care among GPs in the UK. (18) Prior to this study we conducted detailed interviews with 19 Scottish GPs, sampled to maximize diversity of spiritual affiliation, using an approach informed by grounded theory.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most GPs acknowledge the central place that spirituality occupies in personhood, with the bi-directional relationship between spiritual wellbeing and physical health often being evident in our consultations. 2 Many patients are conscious of their spiritual needs and that these may require therapeutic input. 3 Several spiritual care therapies have been developed to respond to these observations.…”
Section: Introductionmentioning
confidence: 99%